Obtaining biogas from manure and coffee pulp beef - Fajardo Muñoz, Sandra; Páez Gracia, Jaime (Revista Universidad de Guayaquil, 2015)
The digestion of the pulp mixture of coffee with cattle manure in anaerobic conditions is a technique effective for the production of biogas as an option to the issue of environmental pollution and the substitutionof fossil fuels in the country. Today at the national level are not properly exploiting resources such as agricultural waste, such as alternative energy sources today. The amount of biogas obtained in the experiment from a base of 22 kg dry pulp, is 104.7 liters, which is an indicator of what could be achieved if all coffee pulp that is wasted in the country was used. The volumes of gas to be obtained, would amount annually to 258,000 cubic meters, which is equivalent to the energy provided by 157,668 liters of gasoline or 370,220 kilowatt / hours of energy. This study lays the foundationfor the development of technological innovation projects aimed at obtaining alternative energy sources, encouraging the Ecuadorian rural sector to think about the need to install their own digesters, and so use the crop wastes and manure from their livestock.
Keywords: Biodigester; Biogas; Agricultural waste; Cattle Manure; Alternative energy source; Coffee pulp